The Controversy of the 1108 Alliance between Muslims and Crusaders of the East (المجلة الدولية للبحوث العلمية, 2024)
Before the First Crusade forces marched to the east in 1097, Muslims were suffering internal strife between the Abbasid caliphate, dominated by the Saljūks, and the Fatimid caliphate of Egypt over Syria. In addition, the Saljūks themselves had endured internal discord since the death of the last great Sultan, Malik-Shāh, in 1092. The Crusaders would succeede in establishing their powers in the east within a few years and threatened Muslims in Syria and Mesopotamia. The kingdom of Aleppo would face a serious threat from the Crusaders of Antioch, while governor of Mosul (Jāwlī) in Mesopotamia would defie his lord the Saljūk Sultan Muhammad’s attempt to suppress him; however, the Crusaders of the east would suffere from internal discord as well. The principality of Antioch was threatening its Crusader neighbor, the County of Edessa. All this dissension would facilitate establishment of a strange alliance in 1108 that joined several different powers differing in religion and purpose. Jawli of Mosul convinced former leaders of Hilla in southern Iraq to join his party with the Crusaders of Edessa and Armenians of Kaysum. This party concentrated their power against the Crusaders of Antioch led by Tancred and his Muslim ally Ridwan of Aleppo.  This analytical study traces the roots of that alliance and shows how it emerged.